Methane-fueled SOFC with traditional nickel-based anode by applying Ni/Al2O3 as a dual-functional layer - Wang, W.; Zhou, W.; Ran, R.; Cai, R.; Shao, Zongping (Elsevier Inc., 2009)
Novel ?-Al2O3 supported nickel (Ni/Al2O3) catalyst was developed as a functional layer for Ni-ScSZ cermet anode operating on methane fuel. Catalytic tests demonstrated Ni/Al2O3 had high and comparable activity to Ru-CeO2 and much higher activity than the Ni-ScSZ cermet anode for partial oxidation, steam and CO2 reforming of methane to syngas between 750 and 850 °C. By adopting Ni/Al2O3 as a catalyst layer, the fuel cell demonstrated a peak power density of 382 mW cm-2 at 850 °C, more than two times that without the catalyst layer. The Ni/Al2O3 also functioned as a diffusion barrier layer to reduce the methane concentration within the anode; consequently, the operation stability was also greatly improved without coke deposition. © 2008 Elsevier B.V. All rights reserved.